Teaching Medical Students to work with Interpreters - Elizabeth Friedman-Rhodes Sandra Hale (JoSTrans: The Journal of Specialised Translation)
Research into Medical Interpreting seems to indicate that there is little understanding of the role of the interpreter and of the interpreting process among medical practitioners. It has been argued that such a situation can lead to negative consequences for the doctor-patient relationship and therefore affect health outcomes (Cambridge, 1999; Tebble 1999; Davidson, 2000; Bischoff, 2003; Angelelli, 2004; Hale, 2007).